The Prevalence of Rotator Cuff Tears: Is the Contralateral Shoulder at Risk?. (April 2014) - Liem, Dennis; Buschmann, Vera Elisa; Schmidt, Carolin; Gosheger, Georg; Vogler, Tim; Schulte, Tobias L.; Balke, Maurice
Background: Rotator cuff tears are a common cause of pain and disability of the shoulder. Information on the prevalence and identification of potential risk factors could help in early detection of rotator cuff tears and improve treatment outcome. Hypothesis: Patients treated for a symptomatic rotator cuff tear on one side have a higher prevalence of rotator cuff tears and decreased shoulder function on the contralateral side compared with an age- and sex-matched group of healthy individuals. Study Design: Case control study; Level of evidence, 3. Methods: One group consisted of 55 patients who had been arthroscopically treated on one shoulder for rotator cuff tear (tear group). In this group, the nonoperated contralateral shoulder was examined. For comparison, the matching shoulder in a control group consisting of 55 subjectively healthy individuals matched by age (±1 year) and sex to the tear group was included. Diagnosis of a rotator cuff tear was made by ultrasound. Outcomes were measured using the Constant score. Results: The prevalence of supraspinatus tears was significantly higher ( P < .0001) in the tear group (67.3%) compared with the control group (11.0%). The Constant score for the activities of daily living subscale, however, was significantly lower (18.4) in the tear group compared with the control group (19.9; P = .012). No other subcategory score nor the overall score showed a significant difference. There was a significantly higher tear prevalence in the tear group of patients aged between 50 and 59 years ( P < .001) and 60 and 69 years ( P = .004). No tear was diagnosed in the control group in individuals younger than 60 years. Conclusion: Patients treated for partial and full-thickness rotator cuff tears have a significantly higher risk of having a tear on the contralateral side and have noticeable deficits in their shoulder function regarding activities of daily living even if the tear is otherwise asymptomatic.